2012
DOI: 10.1115/1.4007366
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Complete Gas Turbine Engine With Wet Compression

Abstract: In this paper, a thorough flow simulation of a small turbojet engine has been carried out to predict the engine performance as a result of water injected at the compressor inlet. Wet compression will not only change compressor performance characteristic map, but also has effects on both the combustor and the turbine sections. The match between the turbojet engine components, that is the compressor, combustor and turbine, will shift to a new operating point. In this paper, we present a steady-state numerical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…However, the P1 method is usually only accurate in media with near-isotropic radiative intensity, and is extremely difficult to be extended to high orders due to the complicated mathematics involved. Only a few numerical simulations for industrial combustor have applied the P1 method as the RTE solver to account for radiative heat transfer [22,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, the P1 method is usually only accurate in media with near-isotropic radiative intensity, and is extremely difficult to be extended to high orders due to the complicated mathematics involved. Only a few numerical simulations for industrial combustor have applied the P1 method as the RTE solver to account for radiative heat transfer [22,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were conducted by Ulrichs and Joos (2006) with free stream conditions of Mach number 0.7 and droplet size having Sauter Mean Diameter of approximately 16-36 µm showed two behaviors of droplets. First, droplets below 10 µm are separated in the latter one-third part of suction surface and second, at the trailing edge a water film is formed which leads to ligament formation whereas, Sun et al (2013) showed that water droplets smaller than 5 µm can achieve complete evaporation upstream of the combustor and bigger droplets have to enter into the combustor to achieve full evaporation. This shows that fine mists should be provided for water injection if full evaporation is needed before the combustor.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the heat action between the droplets and the air flow was a great influence on the flow field, and the droplets were more easily broken in a higher pneumatic load. Sun et al (2012) numerically simulated the droplet motion in the wet compression process; they pointed out that droplets impinging on blades not only affected the movement and breakage of droplets but also caused additional loads on blades. White et al (2004) discovered that the droplet diameter was the main factor of entropy increase in irreversible phase transformation.…”
Section: Introductionmentioning
confidence: 99%